Efficacy and safety of chlorpromazine as an adjuvant therapy for glioblastoma in patients with unmethylated MGMT gene promoter: RACTAC, a phase II multicenter trial - Pace, Andrea; Lombardi, Giuseppe; Villani, Veronica; Benincasa, Dario; Abbruzzese, Claudia; Cestonaro, Ilaria; Corrà, Martina; Padovan, Marta; Cerretti, Giulia; Caccese, Mario; Silvani, Antonio; Gaviani, Paola; et al. (Frontiers in Oncology, 2023)
Drug repurposing is a promising strategy to develop new treatments for glioblastoma. In this phase II clinical trial, we evaluated the addition of chlorpromazine to temozolomide in the adjuvant phase of the standard first-line therapeutic protocol in patients with unmethylated MGMT gene promoter. This was a multicenter phase II single-arm clinical trial. The experimental procedure involved the combination of CPZ with standard treatment with TMZ in the adjuvant phase of the Stupp protocol in newly-diagnosed GBM patients carrying an unmethylated MGMT gene promoter. Progression-free survival was the primary endpoint. Secondary endpoints were overall survival and toxicity. The study is registered as EudraCT #2019-001988-75 and ClinicalTrials.gov Identifier #NCT0422444.Forty-one patients were evaluated. Twenty patients (48.7%) completed 6 cycles of treatment with TMZ+CPZ. At 6 months, 27 patients (65.8%) were without progression, achieving the primary endpoint. Median PFS was 8.0 months (95% CI: 7.0-9.0). Median OS was 15.0 months (95% CI: 13.1-16.9). Adverse events led to reduction or interruption of CPZ dosage in 4 patients (9.7%).The addition of CPZ to standard TMZ in the first-line treatment of GBM patients with unmethylated MGMT gene promoter was safe and led to a longer PFS than expected in this population of patients. These findings provide proof-of-concept for the potential of adding CPZ to standard TMZ treatment in GBM patients with unmethylated MGMT gene promoter.